Scriptorium Berricense: A multidisciplinary experience in Compulsory Secondary Education in Spain (ESO). - González Garzón, Ignacio (Pulso. Revista de educación, 2002)
This multidisciplinary project was conducted with secondary education students from the Berriz School of Las Rozas (Madrid). It focuses on the life of a medieval monastery as a specific context for students to explore various areas of knowledge and curricular content.